Partitioning of copper at the confluences of Andean rivers. (November 2020) - Montecinos, Mauricio; Coquery, Marina; Alsina, Marco A.; Bretier, Marie; Gaillard, Jean-François; Dabrin, Aymeric; Pastén, Pablo
Abstract: The fate of copper (Cu) in rivers impacted by acid drainage remains poorly studied in waters with comparatively low Al and Fe concentrations. This work addresses the role of confluences in controlling the physical and chemical fate of Cu in a system with total molar ratio Cu/Al > 0.2 and Cu/Fe > 0.15. Two consecutive confluences were studied in the upper Mapocho watershed, a densely populated basin with intensive mining located in the Chilean Andes. The inflow had acidic conditions with seasonal variations and Cu up to 9 mg L −1 . Lability measurements with diffusive gradient in thin films showed that Cu entered as a dissolved labile form. However, downstream from the confluences a higher pH shifted Cu toward nonlabile compounds and solid phases enriched with Cu. Measurements of x-ray absorption spectroscopy of freshly formed particles showed that composition was dominated by sorbed Cu and Cu(OH)2 (s) precipitates, with a higher proportion of sorbed Cu downstream from confluences when pH < 5. Particle size distributions (PSD) measured in field showed that downstream from the confluences the total volume and average diameter of the suspended particles grew progressively, with estimated mean settling velocities increasing from 0.3 to 4.2 cm s −1 . As a result, 7–30% of the influent Cu was removed from the river flow. These results highlight that shifts in chemical partition and PSDs in river confluences and the hydrodynamic environments at the river reach level control the mobility of Cu in systems with high Cu/Al and Cu/Fe. Graphical abstract: Image 1 Highlights: Confluences shift the partition of Cu toward particulate compounds. Attenuation of Cu is driven by sorption (pH < 5) and precipitation (pH∼7). Confluences increase the size and volume of Cu-enriched particles. Hydrodynamic processes control mobility and attenuation of Cu.